2007
DOI: 10.4049/jimmunol.178.7.4335
|View full text |Cite
|
Sign up to set email alerts
|

CCL23 Expression Is Induced by IL-4 in a STAT6-Dependent Fashion

Abstract: The chemokine CCL23 is primarily expressed in cells of the myeloid lineage but little information about its regulation is available. In this study, it is demonstrated that IL-4 and IL-13 induced CCL23 expression in human peripheral blood monocytes. GM-CSF had no effect on its own but synergized with IL-4, but not IL-13. CCL23 promoter reporter gene constructs were sensitive to IL-4 stimulation in the presence of the transcription factor STAT6. A canonical STAT6 binding site in the promoter region of the CCL23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 48 publications
1
27
2
Order By: Relevance
“…Previous studies identified the STAT6, NFAT, NF-ĸB, and AP-1 binding sites in the 5′ flanking region of the CCL23 gene [13,14]. However, our results suggest that other transcription factor(s) may be involved in the transcriptional regulation of CCL23 because neither GM-CSF nor IL-5 activates those known transcription factors.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies identified the STAT6, NFAT, NF-ĸB, and AP-1 binding sites in the 5′ flanking region of the CCL23 gene [13,14]. However, our results suggest that other transcription factor(s) may be involved in the transcriptional regulation of CCL23 because neither GM-CSF nor IL-5 activates those known transcription factors.…”
Section: Discussioncontrasting
confidence: 53%
“…While CCL23/MPIF-1 cDNA was originally isolated from a human aortic endothelial library (Patel et al, 1997), subsequent analysis made on various cell lines has shown that CCL23 mRNA is readily detectable in myelomonocytic cell lines (Patel et al, 1997). Expression of CCL23 mRNA was then found in monocytes stimulated with IL-1β (Forssmann et al, 1997) and it is now established that IL-4-treated monocytes produce remarkable amounts of CCL23 (Nardelli et al, 1999; Novak et al, 2007). CCL23 can be detected in synovial fluids from rheumatoid arthritis patients (Berahovich et al, 2005), as well as in serum of systemic sclerosis patients (Yanaba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Within this pathway, the gene most differentially expressed in BRIDGE WB and demonstrating strong replication in CAMP WB was CCL23 (Table 3), an IL4/signal transducer and activator of transcription 6-induced chemoattractant of dendritic cells (31,32). In GSE9988, CCL23 was preferentially up-regulated in LPS-treated monocytes.…”
Section: Novel Biologic Insights Into Asthma Controlmentioning
confidence: 99%